Text‐message reminders plus incentives increase adherence to antidiabetic medication in adults with type 2 diabetes. Issue 4 (14th July 2016) - Raiff, Bethany R.; Jarvis, Brantley P.; Dallery, Jesse
Abstract : Some adults with Type 2 diabetes mellitus have difficulty adhering to their oral medication regimens. The current study used a multiple baseline design with 3 adults with Type 2 diabetes. Medication taking was monitored remotely in real time via an electronic pill bottle. During the intervention, monetary incentives were delivered contingent on evidence of adherence to taking medication at specified times. Text‐message reminders were also sent if medication was not taken. Adherence increased for all participants. Future studies should separate the relative contributions of text‐message and incentive components of the intervention.